DIGITAL TECHNOLOGIES OF CONSUMER IMAGE DEVELOPMENT - ZUBKO, OLGA; SHVETS, GALINA; KULESHOVA, SVITLANA; SELEZNEVA, ANNA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article is devoted to developing wardrobe capsules for the targeted consumer using digital tools and automated design methods that make up the integration strategy for creating fashion innovations for fashion brands in the context of Circular fashion. Technological progress, oversaturation of the market with goods, and the speed of changes in fashion trends are forcing manufacturers to reconsider their development strategy and the vector in which they need to move and develop. Fashion design is one of the activities most dependent on innovation. Especially evident in costume design, the object of which is a person, and the goal is to form an image, taking into account the characteristics of the individual. In recent years, the ecological component of fashion has been carefully studied. Slow fashion, with a focus on quality, design, sustainability and ethics, represents an alternative to fast fashion’s harmful environmental and social impacts. The move towards a circular economy and sustainable development has become increasingly important worldwide in recent years. Awareness of sustainable production and consumption practices is also growing. Upcycling is considered a sustainable approach in several fields, including environmental management, engineering, technology, and design. It is a process in which materials that become old after their use are transformed into higher-quality products. The object of the study is the process of forming the author’s wardrobe assortment capsules based on new innovative design practices. The research subject is digital technologies for developing one’s image using upcycling methods. Approaches to using mobile applications as innovative digital tools for developing wardrobe capsules for the targeted consumer are proposed. The formulated working hypothesis of the study on the possibility of adapting mobile applications for creating a capsule wardrobe, planning and forming an individual image of the consumer was confirmed by the example of many applications and their specific practical application. An algorithm for forming an individual wardrobe has been developed using the methodology of targeted design of garments based on the typology of design images in the fashion industry based on the primary colours of costume ensembles. Based on the classifier’s results, capsules of the real and desired author’s wardrobe were formed, the basis of which are exclusive ensembles of consumer women’s clothing using the upcycling concept. In the context of the work carried out, they represent a means of forming fashion standards and a tool for the mass consumer to implement self-identification in modern fashion.